Pengembangan Media Gambar Seri Berbasis Puzzle Untuk Meningkatkan Kemampuan Menulis Narasi Siswa Kelas IV MI: Development of a Puzzle-Based Picture Series to Improve Narrative Writing Skills Among Fourth-Grade Students at Madrasah Ibtidaiyah - Muliana Fitri Lingga; Andina Halimsyah Rambe (Institut Agama Islam Daruttaqwa Gresik, 2026)
When learning Indonesian at the Madrasah Ibtidaiyah (MI) level, narrative writing is crucial. However, preliminary observations in the classroom showed that many fourth-graders struggled with concept development, story sequence organization, and cohesive written expression. This study sought to address this problem by creating and evaluating puzzle-based image series media as a means of improving MI Yayasan Islam students' narrative writing abilities. Addini. The ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation, was used in this study to establish a Research and Development (R&D) framework. Twenty fourth-graders, one classroom teacher, and two expert validators (media and material specialists) participated in the study. Narrative writing exams (pretest and posttest), expert validation tools, classroom observations, interviews, and answer surveys were the methods used to gather data. The results showed that pupils' proficiency in narrative writing had significantly improved. With an N-Gain value of 0.68 (68%), the average score rose from 42.75 in the pretest to 81.75 in the posttest, indicating moderate to high efficacy. With the media expert receiving an average score of 4.00 and the material expert receiving a feasibility percentage of 82.5%, the validation findings showed that the generated media were highly viable. Additionally, the implementation was well received by both instructors and pupils, as seen by the feasibility percentages of 100% and 85.6%, respectively. All things considered, the puzzle-based image series proven to be successful in boosting learning motivation, developing narrative writing abilities, and promoting active engagement in Indonesian language training. Upcoming research are suggested to involve broader participant groups, extend the implementation period, and integrate digital features to maximize learning outcomes.